Józef Florczak: Prelato Uditore della Rota Romana morto nel Lager Dachau. Parte II - Caberletti, Giordano (Ius Matrimoniale, 2015)
Monsignor Józef Florczak (1885-1943) exercised his priestly ministry in a variety of positions: he was Professor and Dean of the Faculty of Canon Law and Moral Sciences of the University of Lublin, Rector of the Polish National Parish of Saint Stanislaus in Rome, Prelate Auditor of the Roman Rota and Parish Priest. He died in the Dachau concentration camp on the 20th of April 1943. Although his published academic work certainly is not abundant, nonetheless the attention he paid to footnotes clearly shows its scientific value. But where his qualities as a canonist and his wisdom as a judge are most evident, is in the thirty six sentences that Monsignor Florczak wrote as Prelate Auditor of the Roman Rota. The pars in iure of each judgement reveals his great erudition in the areas of Roman Law, theology, canonical tradition, the praxis of Roman Congregations, and of Rotal jurisprudence. In examining the sentences coram Florczak, it seemed preferable to study them according to their varied topics and thus determine their importance. To this end, the main arguments of the treatise are those that concern the different aspects of the nullity of marriage. Other specific arguments are: the invalidity of assuming the onera sacrae ordinationis, a quaestio incidens super contumacia, the competence of tribunals and the restitutio in integrum.